Efektivitas Ekstrak Jahe Merah (Zingiber Officinale Var. Rubrum) Dengan Menggunakan Variasi Tempat Bertengger Dingin Terhadap Indikator Stres Panas Pada Ayam Broiler - M. Adjie Mas Sahid (CV. SINAR HOWUHOWU, 2026)
This study aimed to determine the effects of red ginger (Zingiber officinale var. rubrum) extract supplementation and the use of cooled perches on heat stress indicators in broiler chickens. A total of 198 day-old chicks (DOC) were reared in 18 experimental pens using a completely randomized design (CRD) consisting of three treatments with six replications. The treatments included P1 (control without red ginger extract and without cooled perches), P2 (red ginger extract supplementation without cooled perches), and P3 (red ginger extract supplementation with cooled perches). The observed variables included water intake, total leukocyte count, body temperature, and the heterophil-to-lymphocyte (H/L) ratio. Data were analyzed using analysis of variance (ANOVA), followed by Duncan's multiple range test using SAS software. The results showed that total leukocyte counts did not differ significantly among treatments. However, water intake and body temperature were significantly lower (P < 0.05) in P3 than in P1 and P2 as the birds aged. The H/L ratio in P3 was significantly lower than in P2 and P1, while the H/L ratio in P2 was significantly lower than in P1. It can be concluded that supplementation with red ginger extract, either alone or in combination with cooled perches, improved thermoregulation in broiler chickens reared under high-temperature conditions in semi-open housing systems.